Biodegradable Films Containing Clove or Citronella Essential Oils against the Mediterranean Fruit Fly Ceratitis capitata (Diptera: Tephritidae) - Arancibia, Mirari (2013)
A concentration-response bioassay against the Mediterranean fruit fly, Ceratitits capitata, was performed to evaluate the insecticidal activity of biodegradable films containing clove (Eugenia caryophyllata, Myrtaceae) or citronella (Cymbopogon nardus, Poaceae) oils. We recorded the time of knock down flies after the exposure to soy protein-lignin films incorporated with 3% food grade clove or citronella essential oils, or control films without bioactive. The vapors of clove released from the film containing 3% essential oil were efficient to trigger the tumbling of the flies (40% after 4 h exposition) and after 20 h 90% of the flies died. However, films containing citronella essential oil had poor insecticidal activity. Citronella oil have a much higher insecticidal activity in a pure form, but probably one or both of their main bioactive compounds (citronellal and geraniol) were poorly released from the films. In this work, for the first time, a novel packaging system controlling the release of essential oil of clove with good insecticidal activity against Ceratitits capitata was achieved, that can be used to improve quality of fruit and for food products.